Transvenous Temporary Cardiac Pacing (Rhythmos, 2014)
Transvenous temporary cardiac pacing is a rather old but still contemporary life-saving technique, with a unique value in the treatment of critically ill patients suffering from rhythm disturbances and associated hemodynamic compromise. Physicians involved in the management of such patients should always keep in mind the indications and contraindications of transvenous temporary cardiac pacing, and should be at least familiar with the insertion technique and the post-insertion care.
Keywords: temporary cardiac pacing; transvenous temporary cardiac pacing